An investigation of the dynamic behaviors of an MRE isolator subjected to constant and alternating currents. (24th June 2016) - Shi, H F; Yu, M; Zhu, M; Fu, J; Choi, S B; Xing, Z W
Abstract: This paper presents the dynamic behaviors of a magneto-rheological elastomer (MRE) isolator by applying constant and time-varying exciting currents. As the first step, a shear type of the MRE isolator is devised with a simplified design. Then, the distributions of the magnetic field in the MRE isolator under both constant and alternating exciting currents are analyzed by commercial software (ANSYS). Subsequently, the dynamic performances of the isolator are experimentally evaluated by applying three different inputs: constant, square and sinusoidal exciting current. It has been identified from the experimental results that the constant exciting current can provide optimal performances in static control, while the MRE isolator presents more advantages in dynamic control with the sine wave current excitation. This means that an attenuation coefficient of alternating current should be considered to achieve a better dynamic control effect. On the other hand, it has also been demonstrated that alternating the magnetic field can provide a broader variable range of the viscous damping coefficient than that under constant magnetic field.